Pembacaan Buku Teks Pendidikan Agama Islam dan Budi Pekerti Kelas X SMA dalam Perspektif Toleransi dan Intoleransi Beragama - Zen Amrulah; Moch Fahrur Ridla (AJMIE: Alhikam Journal of Multidisciplinary Islamic Education, 2021)
The Islamic Religious Education textbook ideally functions as a learning media to emerge religious tolerance values to students. However, it is still found that the Islamic Religious Education textbook in elementary and secondary schools contains religious intolerance. Therefore, this article intends to examine the Islamic Religious Education and Character book of  Class X in the perspective of religious tolerance and intolerance. This article is compiled with a qualitative approach, a library research type. The data collection techniques were in the form of documentation and content analysis techniques through hermeneutical meaning that involves the horizon of text and context. The findings of this article are: most of the book contents are in accordance with the values of religious tolerance. However, it is still found such content that has a religious intolerance, precisely in Chapter II regarding intolerance in dressing, Chapter IV related to exclusive thinking, and Chapter X related to radical understanding.Idealnya, buku teks Pendidikan Agama Islam (PAI) berfungsi sebagai media pembelajaran untuk menanamkan nilai-nilai toleransi beragama kepada peserta didik. Realitanya, masih dijumpai pemberitaan yang menyebutkan bahwa buku teks PAI di sekolah dasar dan menengah, mengandung muatan intoleransi beragama. Oleh sebab itu, artikel ini bermaksud menelaah buku PAI dan Budi Pekerti kelas X dalam perspektif toleransi dan intoleransi beragama. Artikel ini disusun dengan pendekatan kualitatif, jenis penelitian pustaka, teknik pengumpulan data berupa dokumentasi dan teknik analisis isi melalui pemaknaan hermeneutis yang melibatkan horizon teks dan konteks. Temuan artikel ini adalah mayoritas isi buku PAI dan Budi Pekerti kelas X SMA sudah sesuai dengan nilai-nilai toleransi beragama. Akan tetapi, masih dijumpai isi buku yang memiliki muatan intoleransi beragama, tepatnya pada Bab II terkait intoleransi dalam berpakaian, Bab IV terkait pemikiran eksklusif, dan Bab X terkait paham radikal.